FATWA DAN ISU SEMASA: MASALAH DAN CABARAN DI MALAYSIA - Ab Majid, Mahmood Zuhdi (Jurnal Syariah, 2019)
Ijtihad has been practiced by Islamic scholars since long time ago in solving several emergent issues. During that time through ijtihad, fatwa has been produced but treated merely as personal opinion. Nowadays, the role of Islamic scholars in producing fatwa in Malaysia is said to have been taken by the government through the appointment of Fatwa Committee. This article discusses the transmission of the role in order to formalize fatwa and to make it binding.